2021
DOI: 10.48550/arxiv.2111.11794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Introduction to Presentation Attack Detection in Face Biometrics and Recent Advances

Abstract: The main scope of this chapter is to serve as an introduction to face presentation attack detection, including key resources and advances in the field in the last few years. The next pages present the different presentation attacks that a face recognition system can confront, in which an attacker presents to the sensor, mainly a camera, a Presentation Attack Instrument (PAI), that is generally a photograph, a video, or a mask, to try to impersonate a genuine user.First, we make an introduction of the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The discovery is essential as the latest models with the most exact results depend on deep-fake learning techniques comprising numerous neural organization boundaries. Reasonable AI in PC vision in this way is an examination heading that is expected to advance and use the advances and focal points of AI and AI in computerized media legal sciences [37][38][39][40][41][42][43][44][45].…”
Section: The Discussionmentioning
confidence: 99%
“…The discovery is essential as the latest models with the most exact results depend on deep-fake learning techniques comprising numerous neural organization boundaries. Reasonable AI in PC vision in this way is an examination heading that is expected to advance and use the advances and focal points of AI and AI in computerized media legal sciences [37][38][39][40][41][42][43][44][45].…”
Section: The Discussionmentioning
confidence: 99%
“…Presentation attack: In presentation attack, FR models are fooled by modifying the human features with the help of artifacts, such as make-up, printed face masks, 3D masks, and accessories. [23][24][25][26] As shown in Fig. 7, the presentation attack is applied using the 3D mask image and eyeglasses to fool the FR models.…”
Section: Introductionmentioning
confidence: 99%
“…Now, face recognition (FR) systems have become an exceptionally accurate technology in identifying people from images (Schroff, Kalenichenko, and Philbin 2015;He et al 2016). While being useful, face recognition may invade the privacy of individuals when used to exploit and process illicitly their face images (Hadid et al 2015;Hernandez-Ortega et al 2021) and videos (Tolosana et al 2022b,a) found on the internet, particularly social media.…”
Section: Introductionmentioning
confidence: 99%